2001
DOI: 10.1128/iai.69.11.7083-7090.2001
|View full text |Cite
|
Sign up to set email alerts
|

Analysis ofBorrelia burgdorferivlsEGene Expression and Recombination in the Tick Vector

Abstract: Expression and recombination of the antigenic variation vlsE gene of the Lyme disease spirochete Borrelia burgdorferi were analyzed in the tick vector. To assess vlsE expression, Ixodes scapularis nymphs infected with the B. burgdorferi strain B31 were fed on mice for 48 or 96 h or to repletion and then crushed and acetone fixed either immediately thereafter (ticks collected at the two earlier time points) or 4 days after repletion. Unfed nymphs also were examined. At all of the time points investigated, spiro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
86
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(93 citation statements)
references
References 34 publications
6
86
0
1
Order By: Relevance
“…It was reported by Ohnishi and de Silva (31) that B. burgdorferi in ticks inoculated by feeding on infected mice contained vlsE sequence variants that either arose within the ticks or were selected during the second feeding. However, vlsE recombination was not detected in recent studies in which ticks were inoculated with B. burgdorferi clone 5A3 by capillary feeding (32). Thus the recombination mechanism appears to be up-regulated in mammalian tissues as compared with either the arthropod or in vitro culture environments.…”
Section: Resultsmentioning
confidence: 84%
“…It was reported by Ohnishi and de Silva (31) that B. burgdorferi in ticks inoculated by feeding on infected mice contained vlsE sequence variants that either arose within the ticks or were selected during the second feeding. However, vlsE recombination was not detected in recent studies in which ticks were inoculated with B. burgdorferi clone 5A3 by capillary feeding (32). Thus the recombination mechanism appears to be up-regulated in mammalian tissues as compared with either the arthropod or in vitro culture environments.…”
Section: Resultsmentioning
confidence: 84%
“…This result suggested that vlsE recombination may be stimulated during nymphal feeding or that the vlsE locus may be subjected to different selective forces within unfed and partially fed nymphs. In a related study, Indest et al (15) used capillary feeding to introduce a clonal population of spirochetes with a single vlsE allele into ticks (15). When capillaryinfected nymphs were tested, only the original allele was detected, indicating that vlsE recombination did not occur within capillary-infected nymphs (15).…”
mentioning
confidence: 99%
“…A few studies have focused on vlsE alleles within infected nymphal ticks (15,24). Individual wild ticks carry spirochete populations with multiple vlsE alleles, which may be indicative of recombination within the tick or the tick acquiring a heter-ogeneous population from the vertebrate host (16).…”
mentioning
confidence: 99%
“…The resulting recombination leads to changes in the sequence of the expression cassette but no alterations in the sequences of the silent cassettes (53). vlsE variation has been shown to occur within 4 days of experimental infection of mice with B. burgdorferi B31 and continues throughout the course of infection but has not been observed in vitro or in the tick vector (21,53,54). The conservation of vls sequences in other strains and species of Borrelia indicate that the vls locus is important for the life cycle of Lyme disease agents (23,25,49).…”
mentioning
confidence: 99%